Demography, habitat use and movements of a recently reintroduced island population of Evermann’s Rock Ptarmigan - Kaler, Robb S.A. (Kansas State University, 2007)
Translocations are a useful management tool for restoring wildlife species to their native ranges, but require post-release monitoring to determine project success. We report results of a 4-year effort to reestablish a breeding population of Evermann's Rock Ptarmigan (Lagopus mutus evermanni) on Agattu Island in the Aleutian Archipelago, Alaska. This endemic subspecies of ptarmigan was extirpated from most of the Near Islands by introductions of arctic fox by fur traders, and natural recolonizations did not occur after fox eradication. All females surviving the 2-week post-release period attempted to nest but initiated clutches later in the season and laid fewer eggs than resident females. Nest success was similar for resident and translocated females. Brood survival was greater for translocated than resident females and differed significantly; however, brood survival varied among years and was reduced by adverse weather conditions in 2006. Seasonal survival of radio-marked birds during the breeding season was 100% for translocated and resident ptarmigan. Over-winter mortality resulted in a low return rate in 2006. Returning birds in 2006 showed strong site fidelity and nest locations in two consecutive years were closely spaced. We examined nest site selection and determined brood movements and home range size of recently translocated and resident females. Nest sites of translocated females averaged 4.2 km from their respective release location and were not different from nest locations of resident females with regard to topographical features. Female nest site selection was influenced by percent composition of rock and forb coverage but was unaffected by slope, aspect, or general habitat. Broods of both resident and translocated females made movements to higher elevations after hatching. While size of brood home range was similar for resident and translocated females, distances traveled between the nest site and the arithmetic center of the brood home range were greater for translocated females. Overall, we conclude that translocations are an effective technique for reestablishing island populations of Rock Ptarmigan. Our study provides successful methods which may benefit future projects to reestablish endemic populations of ptarmigan and landbirds elsewhere in the Aleutian Islands.
Keywords: rock ptarmigan; reproductive success; Agattu Island; translocation; Biology, Ecology (0329)